2005
DOI: 10.1128/jb.187.4.1293-1304.2005
|View full text |Cite
|
Sign up to set email alerts
|

Ectoine-Induced Proteins in Sinorhizobium meliloti Include an Ectoine ABC-Type Transporter Involved in Osmoprotection and Ectoine Catabolism

Abstract: To understand the mechanisms of ectoine-induced osmoprotection in Sinorhizobium meliloti, a proteomic examination of S. meliloti cells grown in minimal medium supplemented with ectoine was undertaken. This revealed the induction of 10 proteins. The protein products of eight genes were identified by using matrixassisted laser desorption ionization-time-of-flight mass spectrometry. Five of these genes, with four other genes whose products were not detected on two-dimensional gels, belong to the same gene cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
119
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(123 citation statements)
references
References 65 publications
3
119
0
Order By: Relevance
“…]; this value is similar to the level found in strain 102F34 in the same experimental conditions (Gouffi et al, 1999;Jebbar et al, 2005;Talibart et al, 1994). Trehalose was not detected in the rpoE2 mutant in the same experimental conditions.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…]; this value is similar to the level found in strain 102F34 in the same experimental conditions (Gouffi et al, 1999;Jebbar et al, 2005;Talibart et al, 1994). Trehalose was not detected in the rpoE2 mutant in the same experimental conditions.…”
supporting
confidence: 74%
“…In contrast, in the absence of osmoprotectants, or in the presence of nonaccumulated osmoprotectants, osmoprotection is achieved by the synthesis and accumulation of glutamate, NAGGN and trehalose (Gouffi et al, 1999;Jebbar et al, 2005). The growth of the rpoE2 mutant is affected in hyperosmotic medium deprived of osmoprotectants or containing nonaccumulated osmoprotectants, suggesting that synthesis of glutamate, NAGGN or trehalose is affected.…”
Section: Osmolyte Content Of Rpoe2 Mutantmentioning
confidence: 99%
“…This result is surprising, since the site-directed change of the Trp residues to either Phe or Tyr residues within the E. coli ProX ligand-binding site has essentially no influence on ligand binding (40). Furthermore, mutational analysis of the aromatic residues within the binding site of the ectoine/hydroxyectoine binding protein EhuB from Sinorhizobium meliloti (14,21) (14). Replacements of these aromatic residues by Trp, the amino acid that has the strongest electronegative potential and is hence best suited for cation-interactions (11,31), created superbinding variants of EhuB that bind both ectoine and hydroxyectoine with K d values in a low nM range (14).…”
mentioning
confidence: 98%
“…bacteria presumably serve as potential sources of ectoine for S. meliloti (1). In addition, ectoine does not accumulate within S. meliloti cells; instead, it is degraded.…”
mentioning
confidence: 99%
“…In addition, ectoine does not accumulate within S. meliloti cells; instead, it is degraded. It has been demonstrated that the ehuABCD-eutABCDE operon is involved in ectoine uptake and catabolism in S. meliloti, and an ABC transporter encoded by four genes (ehuA, ehuB, ehuC, and ehuD) has been reported to be responsible for ectoine uptake in this species (1). The ehuABCD genes form an operon with another cluster of putative ectoinecatabolic genes, previously named eutA, eutB, eutC, eutD, and eutE.…”
mentioning
confidence: 99%